Deliberation before the Revolution: Toward an Ethics of Deliberative Democracy in an Unjust World - Archon Fung (Political Theory 2005; 33; 397, 2005)
Deliberative democracy is a revolutionary political ideal that requires fundamental changes in political institutions, bases of collective decision making, and the distribution of resources. Perhaps because of its revolutionary character, accounts of deliberation in political theory thus far have offered little guidance for actors in actually-existing democratic circumstances. This article develops an ethical account of deliberative democratic action under imperfectly just conditions characterized by material and political inequality and failures of reciprocity. Under such conditions, appropriate principles of action can resolve the tension between deliberation and confrontational political activism. The logic of this account parallels the justification for civil disobedience: the extent of permissible deviation fromdeliberative norms increases according to the adversity of political circumstances. This ethical account is composed of principles of deliberative activism, applications of those principles to four kinds of increasing unfavorable circumstances, and a menu of institutional and political strategies that increase deliberative inclusion and equality